Clinical Characteristics and Outcomes in Patients Undergoing Primary or Secondary Enucleation or Evisceration After Ocular Trauma - Gauthier AC (Dove Medical Press, 2020)
Angela C Gauthier, Oluseye K Oduyale, Michael J Fliotsos, Sidra Zafar, Nicholas R Mahoney, Divya Srikumaran, Fasika A Woreta Wilmer Eye Institute, Johns Hopkins School of Medicine, Baltimore, MD, USACorrespondence: Fasika A WoretaWilmer Eye Institute, Johns Hopkins School of Medicine 600 North Wolfe Street, Baltimore, MD 21205, USATel +1 410-961-2868Fax +1 410-614-9632Email fworeta1@jhmi.eduPurpose: To investigate the frequency of primary versus secondary eye removal, frequency of enucleation versus evisceration, and characteristics and outcomes of patients undergoing these procedures after presenting with severe ocular trauma.Patients and Methods: Retrospective chart review of patients presenting to the emergency department (ED) with severe eye trauma necessitating enucleation or evisceration between 2010 and 2018.Results: There were 92 eyes from 90 patients included in our study. Twenty-seven percent of eyes underwent primary removal (n=25, 14 enucleation, 11 evisceration), while 73% of eyes underwent secondary removal (n=67, 50 enucleation, 17 evisceration). The mean patient age was 45.2 years (range 4.2– 92.6); primary enucleation/evisceration patients were older on average than secondary eye removal patients [53.8 years (range 15.9– 91.2) versus 42.2 years (range 4.2– 91.6 years), p=0.04]. A median of 34 days passed between ED presentation and secondary enucleation/evisceration. Before undergoing secondary enucleation/evisceration, patients underwent a median of one ocular procedure (range 0– 14) for various complications of trauma including orbital infection, choroidal or retinal tear or detachment, and wound dehiscence. Open globe injury repairs comprised 43 of the 92 total procedures (47%) performed prior to secondary enucleation/evisceration. Secondary enucleations/eviscerations required a median of seven clinic visits compared to two clinic visits required after primary surgeries (p< 0.01). 10.7% of all patients (n=10) had at least one implant-related complication following enucleation/evisceration, with all but one of these patients being in the secondary enucleation/evisceration group.Conclusion: Primary enucleation or evisceration was performed in 27% of all eye removals, and enucleation was performed in 69.6% of all eye removals. Future research is warranted to determine if primary eye removal may be appropriate and when to consider enucleation versus evisceration.Keywords: evisceration, enucleation, open globe repair, traumatic eye injury